Multiple regulation of ornithine decarboxylase in enzyme-overproducing cells. - Kameji, T (1993)
We have isolated from mouse FM3A cells a variant cell line, termed EXOD-1, that overproduces ornithine decarboxylase (ODC). The cells were resistant to alpha-difluoromethylornithine, an irreversible inhibitor of the enzyme, and produced the enzyme protein to the extent of approx. 3-6% of total cytosolic protein. The rate of ODC synthesis in this cell line accounted for 25-50% of the rate of total protein synthesis. The amounts of the ODC gene and its mRNA in the variant cells were both about 60 times as much as those in wild-type FM3A cells. Upon removal of the inhibitor, the growth of the ODC-overproducing cells was stimulated approx. 2-fold. Under these conditions, the rate of ODC synthesis increased about 4-fold on day 1 and then decreased to near the original level by day 3. The amount of ODC mRNA increased about 1.7-fold on day 1 and 2.5-fold on day 3. No correlation was observed between changes in ODC synthesis rate and in ODC mRNA content, suggesting a translational repression of ODC mRNA due to accumulation of polyamines. In fact, the cellular contents of putrescine and spermidine markedly increased and that of spermine inversely decreased during the same period. Pulse-chase experiments showed that the accumulation of putrescine and spermidine also elicited a rapid degradation of ODC. Excess amounts of newly synthesized putrescine and cadaverine were excreted into the medium, whereas spermidine, spermine and acetylated polyamines were undetectable there. We conclude that ODC regulation upon removal of the inhibitor is dependent on at least three steps, namely the level of mRNA, the translational efficiency of mRNA and the stability of the enzyme, the last two of which are involved in cellular polyamines.